2008
DOI: 10.2144/000112820
|View full text |Cite
|
Sign up to set email alerts
|

A Quick in Vitro Pathway from Prokaryotic Genomic Libraries to Enzyme Discovery

Abstract: Screening of prokaryotic genomes in order to identify enzymes with a desired catalytic activity can be performed in vivo in bacterial cells. We propose a strategy of in vitro expression screening of large prokaryotic genomic libraries based on Escherichia coli cell-free transcription-translation systems. Because cell-based expression may be limited by poor yield or protein misfolding, cell-free expression systems may be advantageous in permitting a more comprehensive screen under conditions optimized for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…We also demonstrated that multiple ORFs can be expressed successfully from a single, multicistronic DNA fragment. Altogether our cell-free approach allows for the screening of a library of more than 5000 different enzyme variants within less than one day [21].…”
Section: Screening Natural Biodiversitymentioning
confidence: 99%
“…We also demonstrated that multiple ORFs can be expressed successfully from a single, multicistronic DNA fragment. Altogether our cell-free approach allows for the screening of a library of more than 5000 different enzyme variants within less than one day [21].…”
Section: Screening Natural Biodiversitymentioning
confidence: 99%